(untitled) (Huellas, 2016)
In the last decades, transformations in the rural sector set out challenges to think the current dynamics that underlies it; among other things, related to the production model that has been defined, to the processes that different stakeholders directly related to the activity have gone through, and to the socio-economic dynamics linked to the rural sector that unfold and their impact on local spaces. This paper reflects on what has happened in rural Argentina, particularly in the Pampas Region, in relation to these problems. The paper starts by considering some transformation processes that have taken place in the rural sector at a global level to analyse, then, the dominant trends of the rural sector in the Pampas region that allow us to affirm that a new model of agricultural development has been introduced. On the basis of various antecedents, the paper will then present a conceptual proposal to address the problem of the territorial dynamics of the rural actors, the economic aspects and their incidence on local spaces. This dynamics has not been studied specifically from this perspective, and emphasizes the economic-productive elements implied in the constructions, deconstructions and reconstructions of territories, resorting to the notion of capital circulation of the rural actors which constitutes a relevant point to understand the processes that emerge today in agricultural development.